IMPROVING STUDENTSâ SPEAKING ABILITY BY USING PICTURE: A Classroom Action Research at the Tenth Grade Students of SMA Negeri 3 Ketapang in the Academic Year 2013/2014 - Nurvitasari, Heni (West Kalimantan Scholars: Studies on English Language and Education, 2014)
The purposes of this research were to find out whether picture can improve the studentsâ speaking ability or not and to know how well picture can improve the ability of students of the tenth grade of SMA Negeri 3 Ketapang. The subject of the research was the tenth grade students of SMA Negeri 3 Ketapang in the Academic year 2013/2014 who consisted of 30 students. The design of this research was classroom action research. Through observation checklist table and field note, the studentsâ action was observed and reflected in every cycle. Then, the teacher prepared to treat the problem being found. In assessing studentsâ performance, the speaking test was served by the teacher in order to know how significant of the studentsâ improvement. The researcher found that composite picture could improve studentsâ speaking ability. It was showed by the change of studentsâ behavior during the treatment. In which, they showed their passive actions in the first cycle and it turned out to be active actions in the next cycle. They also showed their creativities during the class. As a result, composite picture was successfully solved the studentsâ problem in speaking ability.